2010
DOI: 10.1016/j.bbcan.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of prostacyclin synthase and thromboxane synthase signaling in the development and progression of cancer

Abstract: Prostacyclin synthase and thromboxane synthase signaling via arachidonic acid metabolism affects a number of tumor cell survival pathways such as cell proliferation, apoptosis, tumor cell invasion and metastasis, and angiogenesis. However, the effects of these respective synthases differ considerably with respect to the pathways described.While prostacyclin synthase is generally believed to be pro-tumor, an anti-carcinogenic role for thromboxane synthase has been demonstrated in a variety of cancers. The balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 173 publications
6
54
0
1
Order By: Relevance
“…to an increase in apoptosis regardless of cell type, which is supported by the previous reports showing that inhibition of TxAS resulted in apoptosis in bladder (Moussa et al, 2008a) and lung (Cathcart et al, 2010) cancer cells, and that treatment with TxA 2 receptor antagonists also caused significant apoptosis in bladder cancer cells (Moussa et al, 2008b).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…to an increase in apoptosis regardless of cell type, which is supported by the previous reports showing that inhibition of TxAS resulted in apoptosis in bladder (Moussa et al, 2008a) and lung (Cathcart et al, 2010) cancer cells, and that treatment with TxA 2 receptor antagonists also caused significant apoptosis in bladder cancer cells (Moussa et al, 2008b).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the bladder cancer cells transfected with b-isoform of TxA 2 receptor and stimulated with U46619 resulted in a significant increase in cellular growth rate and PCNA expression (Moussa et al, 2008b). A recent study has also reported that treatment of two NSCLC cell lines with another selective TxAS inhibitor ozagrel induced a significant reduction in cell proliferation (Cathcart et al, 2010). We have further demonstrated that the inhibitory effect of furegrelate or SQ29548 on NNK-promoted cell proliferation/survival is in part due Figure 5 Effects of blocking TxA 2 synthesis and action on Akt, ERK, JNK and p38 in cells exposed to NNK.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been known that PGD 2 and PGI 2 are anticarcinogenic agents (Keith et al, 2004;Park et al, 2007;Cathcart et al, 2010). PGD 2 is rapidly metabolized to 15-deoxy-D 12,14 -PGJ 2 , which inhibits tumor growth via a peroxisome proliferator-activated receptor g (PPARg)-dependent or -independent pathway (Scher and Pillinger, 2005;Mansure et al, 2009).…”
Section: Resultsmentioning
confidence: 99%